Cysticercosis-related mortality in the State of São Paulo, Brazil, 1985-2004: a study using multiple causes of death Tendência da mortalidade relacionada à cisticercose no Estado de São Paulo, Brasil, 1985 a 2004: estudo usando causas múltiplas de morte - Augusto Hasiak Santo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
Cysticercosis-related mortality has not been studied in Brazil. Deaths recorded in the State of São Paulo from 1985 to 2004 in which cysticercosis was mentioned on any line or in any part of the death certificate were studied. Causes of death were processed using the Multiple Cause Tabulator. Over this 20-year period, cysticercosis was identified in 1,570 deaths: as the underlying cause in 1,131 and as an associated cause of death in 439. Standardized mortality rates with cysticercosis as the underlying cause showed a downward trend and were higher among men and older individuals. Intracranial hypertension, cerebral edema, hydrocephalus, inflammatory diseases of the central nervous system, and cerebrovascular diseases were the main associated causes in deaths due to cysticercosis. AIDS was the principal underlying cause of death in which cysticercosis was an associated cause. The counties (municipalities) with the most cysticercosis-related deaths were São Paulo, Campinas, Ribeirão Preto, and Santo André. Wide variation was observed between counties regarding the value ascribed to cysticercosis as the underlying cause of death. This leads to underestimation of the disease's importance in planning health interventions. A mortalidade relacionada à cisticercose na população não tem sido pesquisada no Brasil. Foram estudados os óbitos registrados entre 1985 e 2004 no Estado de São Paulo em que a cisticercose foi mencionada em qualquer linha ou parte da Declaração de Óbito. As causas de morte foram processadas pelo Tabulador de Causas Múltiplas. No período de vinte anos ocorreram 1.570 óbitos, sendo a cisticercose causa básica em 1.131 e causa associada de morte em 439. Os coeficientes padronizados de mortalidade por cisticercose como causa básica apresentaram tendência de declínio, foram maiores entre os homens e nas idades mais avançadas. As principais causas associadas nas mortes por cisticercose foram hipertensão intracraniana, edema cerebral, hidrocefalias, doenças inflamatórias do sistema nervoso central e doenças cerebrovasculares. A AIDS foi a principal causa básica nas mortes com a cisticercose como causa associada. Os municípios com maior número de mortes foram São Paulo, Campinas, Ribeirão Preto e Santo André. Observou-se grande variação entre os municípios na valorização da cisticercose como causa básica de morte, determinando sua subestima para subsidiar o planejamento de políticas de saúde.